The art of make-up and its relation to personality play: زيد سالم سليمان (Al-Academy, 2016)
It is well known that the art of theater is based on multiple elements come in the forefront of Representative and his work, and must be of such a representative of the kits help him to complete his work and take it out the image that aspires to it is team work, and these supplies are in the two main axes:First: Internal supplies which runs from the imagination through the focusing and memory Representative and adapts to situations and positions and others.The second is a foreign supplies, which starts from his words and gestures and his movement and his voice, which is the need to requirements help to maturation and completion of this aspect, including the lighting, costumes, decor, make-up, is the role of make-up theater and its importance, just as important as the role of movement or expression, or sound, nor particularly in relation to character play, which will shed light upon our study tagged (the art of make-up and its relation to personality play)